King Arthur - Retold by Hardy-Gould, Janet and Illustrated by Rator, Axel (Oxford, New York Oxford University Press, 2008)
Word count 1,140 Suitable for young learners
Include Color Illustration
Keywords: Arthur, King -- Readers (Adult) -- Reading comprehension